Nilai-nilai Filosofis Lingkungan Hidup dalam Karya A. Sonny Keraf - Rezeki, Sri Putri; Sukiman, Sukiman; Faza, Abrar M. Dawud (Lembaga Yasin AlSys, 2023)
The environment has become a new area of focus for Sonny Keraf, who previously primarily focused on legal and corporate ethics. Sonny Keraf only began to think about environmental issues after realizing that the current environmental catastrophe actually results from a fundamental philosophical mistake in how people view themselves, nature, and their place in the larger ecosystem. This research uses a historical-factual research methodology on characters and is categorized as philosophical research. The methodological steps of this study's data analysis strategy, which employs the philosophical hermeneutic approach, are interpretation, historical continuity, description, and heuristics. This study demonstrates that; 1) According to A. Sonny Keraf's notion of environmental philosophy, the environment is defined as an oikos, which is a Greek word that implies a place to dwell. However, an oikos is not just a house where people live. Oikos is understood as the entirety of the cosmos, including all of the interactions that take place inside between other living creatures and with the habitat's ecology. Realizing this, Keraf created three paradigms-the Holistic-Ecological Paradigm, the Ecoliteracy Paradigm, and the Biogregionalism Paradigm-to address the environmental problem that humanity is currently facing. 2) The environmental ideals included in the writings of A. Sonny Keraf, including: reverence for nature; moral responsibility for nature; cosmic solidarity; caring for nature; and no harm to the environment.